Edukasi tentang Hipertensi dan Pemeriksaan Tekanan Darah pada Masyarakat Meselesek Kabupaten Banggai Kepulauan - Restawan, I Gede; Sepang, Janice; Matongka, Yulian Heiwer (Jurnal Abdimas Kesehatan (JAK), 2024)
Hypertension or high blood pressure is still a health problem throughout the world. In Central Sulawesi province, hypertension is the disease with the highest number of non-communicable diseases. Likewise, in Banggai Islands Regency, the highest case of non-communicable disease is hypertension and only 6.4% routinely control their blood pressure through existing health services. Hypertension that is left untreated and not treated properly will cause various dangerous complications and even cause death. By looking at this problem, efforts need to be made to help lower blood pressure in hypertension sufferers. One way is to provide information and knowledge about the dangers of hypertension. So, people will be more alert and increase awareness to overcome the problem of hypertension. Therefore, through this community service, the efforts made are to provide health education about hypertension and blood pressure checks direct of people in Meselesek village, Bulagi District, Banggai Islands Regency, Central Sulawesi Province. The results of this community service showed that many people suffered from hypertension, namely 44.28% of all participants who attended. The community also actively asked questions during the health education process and stated that they wanted to get antihypertensive medication. Health education activities and measuring blood pressure in the community are very important to prevent an increase in prevalence, control blood pressure and prevent complications.